Towards Social Transformation Approach to the Eighth Five Year Plan 1990-95 - Planning Commission (Planning Commission Government of India, 1990)
The Eighth Five Year Plan (1990–95) marked a significant shift in India’s development strategy, emphasizing equity, employment, and human development over mere growth indicators. Recognizing persistent socio-economic disparities, rising unemployment, and fiscal inefficiencies, the Plan sought to reorient development towards poverty alleviation, rural upliftment, and decentralised planning. Central to its approach was the concept of the right to work, minimum wage employment, and expanded access to essential social services such as health and education. The Plan prioritized sustainable development, social justice, and the empowerment of marginalized groups, including Scheduled Castes, Scheduled Tribes, women, and the urban poor. It advocated greater public investment in rural areas, land reforms, and improved infrastructure while encouraging technological advancement and export promotion, particularly of labour-intensive goods. Overall, the Eighth Five Year Plan aimed to foster inclusive growth through people-centric policies, strengthened local governance, and balanced economic and social development.
Meeting of The National Development Council 18-19 June 1990, Planning Commission Government of India May 1990
Meeting of The National Development Council 18-19 June 1990, Planning Commission Government of India May 1990
Keywords: Eighth Five Year Plan; Democratic Development; Poverty Alleviation; Employment Generation; Rural Development; Decentralised Planning; Social Justice; Sustainable Development; Human Resource Development; Infrastructure Development; Fiscal Reforms; Export Promotion